Phenotyping animal models of diabetic neuropathy: a consensus statement of the diabetic neuropathy study group of the EASD (Neurodiab). Issue 2 (June 2014) - Biessels, G.J.; Bril, V.; Calcutt, N.A.; Cameron, N.E.; Cotter, M.A.; Dobrowsky, R.; Feldman, E.L.; Fernyhough, P.; Jakobsen, J.; Malik, R.A.; Mizisin, A.P.; Oates, P.J.; et al.
Abstract NIDDK, JDRF, and the Diabetic Neuropathy Study Group of EASD sponsored a meeting to explore the current status of animal models of diabetic peripheral neuropathy. The goal of the workshop was to develop a set of consensus criteria for the phenotyping of rodent models of diabetic neuropathy. The discussion was divided into five areas: (1) status of commonly used rodent models of diabetes, (2) nerve structure, (3) electrophysiological assessments of nerve function, (4) behavioral assessments of nerve function, and (5) the role of biomarkers in disease phenotyping. Participants discussed the current understanding of each area, gold standards (if applicable) for assessments of function, improvements of existing techniques, and utility of known and exploratory biomarkers. The research opportunities in each area were outlined, providing a possible roadmap for future studies. The meeting concluded with a discussion on the merits and limitations of a unified approach to phenotyping rodent models of diabetic neuropathy and a consensus formed on the definition of the minimum criteria required for establishing the presence of the disease. A neuropathy phenotype in rodents was defined as the presence of statistically different values between diabetic and control animals in 2 of 3 assessments (nocifensive behavior, nerve conduction velocities, or nerve structure). The participants propose that this framework would allow different research groups to compare and share data, with an emphasis on data targeted toward the therapeutic efficacy of drug interventions.